Depletion of 14-3-3 proteins in bloodstream-form Trypanosoma brucei inhibits variant surface glycoprotein recycling - Benz, Corinna; Hillmer, Stefan; Clayton, Christine (International journal for parasitology, 2010)
Bloodstream-form Trypanosoma brucei have two 14-3-3 proteins, which are required for parasite multiplication. We here describe the effects of 14-3-3 depletion on vesicular transport of variant surface glycoprotein (VSG). 14-3-3 depletion had no detectable effect on de novo synthesis and trafficking of VSG to the cell surface, or on VSG endocytosis. Despite strong inhibition of cell division, the flagellar pocket was not enlarged and the ultrastructure of internal organelles appeared normal. The Rab11-positive recycling endosome compartment was, however, fivefold smaller than normal, and the rate of return of recycling VSG to the surface was correspondingly reduced. Down-regulating 14-3-3 also prevented enlargement of the flagellar pocket by clathrin depletion. These results suggest that there is a remarkably specific requirement for 14-3-3 in normal functioning of the Rab11-positive recycling endosome compartment.